"I Think That Sometimes Reading Is Overrated": Tactical, Strategic, and Epistemological Reflections on Planning Education. (December 2014) - Sturzaker, John
This article uses the analogy of tactical and strategic planning to suggest methods for increasing the amount of reading done by planning students, inspired by data revealing disappointingly low levels of reading among students at one institution. The article also advocates reflection on teaching and learning practices at an epistemological level, questioning whether the teaching practices of planning scholars have completed the transition to a constructivist epistemology implied by much of the research within the discipline.